The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11999-008-0694-5
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Contractile Gene (TNNT3, MYH3, TPM2) Mutations Not Found in Vertical Talus or Clubfoot

Abstract: Arthrogryposis presents with lower limb contractures that resemble clubfoot and/or vertical talus. Recently, mutations in skeletal muscle contractile genes MYH3 (myosin heavy chain 3), TNNT3 (troponin T3), and TPM2 (tropomyosin 2) were identified in patients with distal arthrogryposis DA2A (Freeman-Sheldon syndrome) or DA2B (Sheldon-Hall syndrome). We asked whether the contractile genes responsible for distal arthrogryposis are also responsible for cases of familial clubfoot or vertical talus. We determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
0
29
0
2
Order By: Relevance
“…PITX1 is the first gene implicated in clubfoot that explains the specific involvement of the foot, since PITX1 is expressed nearly exclusively in the hindlimb and is responsible for rapid evolutionary changes in pelvic morphology in lower vertebrates [58]. Specific involvement of the foot also appears to exclude many of the skeletal muscle contractile genes that are responsible for distal arthrogryposis [62,63,65,70] in the causation of idiopathic clubfoot, as mutations in these genes cause both upper and lower extremity involvement and were not identified in idiopathic clubfoot patients [29].…”
Section: Etiologymentioning
confidence: 99%
“…PITX1 is the first gene implicated in clubfoot that explains the specific involvement of the foot, since PITX1 is expressed nearly exclusively in the hindlimb and is responsible for rapid evolutionary changes in pelvic morphology in lower vertebrates [58]. Specific involvement of the foot also appears to exclude many of the skeletal muscle contractile genes that are responsible for distal arthrogryposis [62,63,65,70] in the causation of idiopathic clubfoot, as mutations in these genes cause both upper and lower extremity involvement and were not identified in idiopathic clubfoot patients [29].…”
Section: Etiologymentioning
confidence: 99%
“…As demonstrated here with MYH3, disease-associated gene variations are gradually being shown to be responsible for an expanded range of phenotypes as exome sequencing technology identifies mutations that are also found in patients with related disorders. Although MYH3 mutations are uncommon causes of isolated clubfoot 10,23 , the diagnosis of distal arthrogryposis should be considered when hand contractures (even those that develop during adolescence) are present in any family members or when the clubfoot is severe and resistant to treatment. Although MYH3 sequencing is currently available as a single-gene genetic test 24 , we anticipate that extended gene panels or exome-based sequencing will soon be available for musculoskeletal disorders such as distal arthrogryposis.…”
Section: Exo M E S E Q U E N C I N G I D E N T I F I E S a N Myh3 Mutmentioning
confidence: 99%
“…Although MYH3 mutations account for nearly all cases of FreemanSheldon syndrome (type 2A) and nearly one-third of all cases of Sheldon-Hall syndrome (type 2B), to our knowledge MYH3 mutations have not been described in patients with distal arthrogryposis type 1 4 . Previous studies have shown that mutations in known genes are rare causes of distal arthrogryposis type 1 9,10 ; therefore, genetic heterogeneity is expected and additional causative genes remain to be identified.…”
mentioning
confidence: 99%
“…[34,35] Bunlar, distal artrogripozisten sorumlu tutulmakla birlikte, bunların mutasyonlarında hem alt hem üst ekstremiteyi ilgilendiren bulgular ortaya çıkmaktadır ki idiyopatik PEV'de bunlar görülmemek-tedir. [36] "Yaygın hastalık -Yaygın Genetik Varyant Hipotezi"ne göre (sıklığı >%5 olan bir alel gen üzerinde bulunan tek nükleotid polimorfizmi); sık görülen genetik varyantların her birinin PEV duyarlılığını arttırmaya küçük çalışmaların sonuçları popülasyona bağlı olarak değişmekle birlikte, PEV'le beraber görülen konjenital anomali veya kromozomal bozukluk sıklığı %24-50 arasında değişmektedir. [43,44] PEV'in bilinen etiyolojileri arasında en sık sinir sistemiyle ilişkili hastalıklar olup, bunlar arasında da en yaygın olanları artrogripozis ve miyelomeningoseldir.…”
Section: Embri̇yoloji̇k çAlişmalarunclassified